Orthopaedic pathology - Vigorita, Vincent J. (Wolters Kluwer, 2016)
"The updated third edition of Orthopedic Pathology is a comprehensive, practical guide to diagnosing musculoskeletal disorders, offering details on the pathologic and radiologic characteristics of all bone and joint diseases. Highlighted by more than 1,700 high-quality illustrations, it focuses on helping you reach an accurate diagnosis for virtually any orthopedic disorder you're likely to encounter."--Back cover.